2021
DOI: 10.1038/s41467-021-23281-y
|View full text |Cite
|
Sign up to set email alerts
|

Infant gut microbiome composition is associated with non-social fear behavior in a pilot study

Abstract: Experimental manipulation of gut microbes in animal models alters fear behavior and relevant neurocircuitry. In humans, the first year of life is a key period for brain development, the emergence of fearfulness, and the establishment of the gut microbiome. Variation in the infant gut microbiome has previously been linked to cognitive development, but its relationship with fear behavior and neurocircuitry is unknown. In this pilot study of 34 infants, we find that 1-year gut microbiome composition (Weighted Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 107 publications
(93 reference statements)
1
67
2
1
Order By: Relevance
“…The complex microbiome on and within a host, critically linked with health and well-being, is referred to as the “second genome” of the host [ 1 ]. This “second genome” is not innate, but is derived from microbial dispersal and affects the growth [ 2 , 3 ], immunity [ 4 ], behavior and cognitive abilities of the host [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex microbiome on and within a host, critically linked with health and well-being, is referred to as the “second genome” of the host [ 1 ]. This “second genome” is not innate, but is derived from microbial dispersal and affects the growth [ 2 , 3 ], immunity [ 4 ], behavior and cognitive abilities of the host [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear is an emotional and behavioral response induced by a threat. Fear is considered an evolutionarily conserved mechanism that promotes survival (Carlson et al, 2021;Lau et al, 2021). A recent study found that babies with less balanced gut microbiomes show an increase in fear behavior in comparison to those with more balanced microbiomes (Carlson et al, 2021;Lau et al, 2021).…”
Section: Microbiome Role In Fear Responsementioning
confidence: 99%
“…Fear is considered an evolutionarily conserved mechanism that promotes survival (Carlson et al, 2021;Lau et al, 2021). A recent study found that babies with less balanced gut microbiomes show an increase in fear behavior in comparison to those with more balanced microbiomes (Carlson et al, 2021;Lau et al, 2021). Gut microbiome communities dominated by Bacteroides at the first year of age are associated with less non-social fear, while the lower abundance of Bacteroides and increased abundance of Veillonella, Dialister, Bifidobacterium, and Lactobacillus were linked to increased fear behavior (Carlson et al, 2021;Lau et al, 2021).…”
Section: Microbiome Role In Fear Responsementioning
confidence: 99%
“…Ref. [ 84 ] showed an association of the human infant gut microbiome with fearful behavior and the microbiome’s relationship with fear-related brain structures. On the other hand, the effects of the gut microbiome on the brain and stress have been reported in animal studies.…”
Section: Stress and Gut Microbiomementioning
confidence: 99%
“…They showed that there were changes in gut microbiota, increases in cytokine expression in the frontal cortex, anxiety-like behaviors, and impaired social behaviors [ 89 ]. The fearful behaviors and related neurocircuitry was changed in animal models, which their gut microbes manipulated [ 84 ]. On the other hand, early life stress can also lead to the gut–brain axis alterations that may contribute to stress-related and psychiatric disorders development in adulthood [ 37 ].…”
Section: Stress and Gut Microbiomementioning
confidence: 99%